[PP.06.05] RELATIONSHIP BETWEEN URIC ACID AND BLOOD PRESSURE LEVELS IN GENERAL POPULATION. (September 2016) - Simonini, M.; Lanzani, C.; Citterio, L.; Brioni, E.; Carpini, S. Delli; Pozzoli, S.; Casamassima, N.; Manunta, P.
Abstract : Objective: Elevated plasmatic levels of uric acid (UA) were frequently associate with hypertension however its role in hypertension pathogenesis is unclear. Design and method: Our aim is to investigate the role of UA on blood pressure (BP) and its genetic determinates on a general population (not treated) of 1350 patients undergoing 24 h ambulatory BP monitoring (AMBP). Results: As expedited, we found of correlation between systolic and diastolic mean 24 h BP values with age (p < 0.001), sex (p = 0.004), BMI (p < 0.001) and plasmatic levels of creatinine (p = 0.023). We also find a strong correlation of BP with UA alone (p = 0.001). Only age and UA remain significant in multivariate analysis with all elements under investigation (respectively p = 0.01 and p = 0.04). We found that UA plasmatic levels are associated with sex (multivariate analysis: p < 0.001), BMI (p = 0.004), renal function (p = 0.001) and with genetic polymorphisms of Protein Kinase CGMP-Dependent Type I (PRKG) and lanosterol synthase (LSS) genes (respectively p = 0.025 and p = 0.05 after correction for clinical covariates included sex, BMI and creatinine level). Conclusions: Our data confirm that UA levels are a strong and independent determinant of BP (both systolic and diastolic) in the general population. Moreover it seems to be an independent element of metabolic syndrome. Finally, UA plasmatic levels are strictly associated with specific clinical and genetic characteristic. In particular we identify two new genes that could play a substantial role in determination of UA plasmatic level.